The power of sharing the case of Sederhana (SA) restaurants in Indonesia - Muhammad Akhyar Adnan (Jurnal Akuntansi dan Auditing Indonesia, 2023)
This paper aims to investigate and describe how the practice of sharing system is applied in one of Indonesia’s well-known and largest indigenous restaurant chains. The research applies a case study method. It is focused only on a single company with around two hundred branches nationwide. The data were mainly collected by deep interviews and observations. All data are analysed qualitatively. An interactive model as suggested by Miles and Huberman (1994) is adopted. The study found that this company has a very distinctive method not only for its financial matters, but also the operations in general. The operations seem to apply the mixed musharaka and mudharaba principles; although the Islamic term is hardly used, the values applied are Islamic in nature. The business model can offer widely that there is another model of business which promises the power of sharing among the participants.